Single-Fluid Approach to Modeling Dark Matter and Dark Energy - Pillay, Vineshree (Department of Mathematics and Applied Mathematics, 2025)
Cosmological observations over the past decades have provided overwhelming evidence for the ex istence of dark energy, a mysterious and dominant component responsible for the accelerated expan sion of the universe. The nature of dark energy remains one of the most intriguing puzzles in modern cosmology. This dissertation presents a comprehensive investigation into the class of Unified Dark Energy Models (UDE), which offer a novel approach to understanding the nature of dark energy by unifying it with other cosmic components, in our case dark matter. The first part of this work reviews the theoretical background and observational evidence for dark energy, highlighting the challenges posed by the cosmological constant and other early models. Next, we present an in-depth analysis of various Unified Dark Energy Models proposed in the literature. The Generalized Chaplygin gas and the Logotropic model. Furthermore, we explore the impact of Unified Dark Energy Models on the large-scale structure of the universe and its evolution at the perturbed level. Following this review we look at a newly proposed equation of state "The Murnaghan equation of state" which accounts for both pressure and matter in the early universe, and exhibits Chaplygin-like behaviour in the later universe. The findings of this study contribute significantly to our understanding of dark energy and its interactions with other cosmic components.